Attitudes toward dementia and cognitive aging among Syrian refugees resettled in Jordan: a qualitative study - Lana Bridi; Dahlia A. Kaki; Rawnaq Behnam; Xara Khan; Behnan Albahsahli; Nissma Bencheikh; Raghad Aljenabi; Nargis Ahmadi; Rana Dajani; Tala Al-Rousan (BMC, 2023)
Abstract Background Mounting evidence is revealing disparities in cognitive function and heightened dementia risk among refugees, yet research in this area remains scant. Despite bearing most of the world's refugee burden, limited-resource countries like Jordan are facing challenges when dealing with refugee health. There is a lack of research on the attitudes toward dementia and the cognitive healthcare gaps among refugees in Jordan. Methods 32 older (≥ 55 years) Syrian refugees resettled in Jordan were recruited through a local community-based organization and interviewed in four focus groups (2 female and 2 male groups). Interviews were transcribed and translated, then coded using inductive thematic analysis. Results Mean age of the sample was 60.1 years and 53.1% were female. Only 34.4% rated their memory as good or excellent. Themes were organized using the socioecological model: 1) At the individual level, participants believed high levels of stress, including low socioeconomic status, poor health, and traumatic history from their refugee experience increased their dementia risk. 2) Interpersonally, there is a fear of dementia due to the possible impact and burden on loved ones, particularly with the stigma surrounding dementia. 3) At the community level, participants noted that resettlement in Jordan - with a shared language, religion, and culture - offered protective effects due to facilitated access to social connection, information, and mental health self-care. 4) At the institution and policy level, participants believed older refugees faced restrictive policies for economic aid, healthcare, and employment, presenting a significant barrier to healthy aging. Conclusions Findings from this study are the first to examine the attitudes of Syrian refugees in Jordan toward dementia and cognitive aging. These results could provide essential data inclusive of refugees as Jordan develops its National Dementia Plan. Investing in dementia awareness interventions and age-friendly neighborhoods may benefit aging refugees in limited-resources settings.